Estimations of the upper and lower depth limits for kerogen to generate oil/gasworldwide: A hypothesis. (22nd April 2023) - Du, Shuheng; Zhao, Ya-Pu; Sun, Fuqiang; Shi, Yongmin
Abstract: This study focuses on the upper and lower depth limits for kerogen to generate oil/gas worldwide. For the first time, the upper and lower depth limits of the conversion process from kerogen to oil/gas are given by the equations with clear physical significance. The method for obtaining the parameters in the equations is also proposed. The results show that the upper limit of hydrocarbon generation of kerogen mainly depends on the ratio of the minimum dissociation energy and initial molar mass of hydrocarbon generation. The smaller the ratio is, the shallower the upper limit of hydrocarbon generation of kerogen is. The upper depth limit of hydrocarbon generation ranges from 688 m to 4925 m, with an average of 1944 m. The lower limit of hydrocarbon generation mainly depends on the ratio of the dissociation energy and molar mass at the end of hydrocarbon generation. The lower depth limit of hydrocarbon generation is proportional to the above ratio. The lower limit of hydrocarbon generation of kerogen ranges from 2539 m to 16 337 m, with an average of 6926 m. This study not only solves a major controversial issue which is the minimum and maximum depth of drilling required to capture oil/gas but also helps select the location of carbon storage. It will be conducive to the effective utilization of fossil energy and the early realization of global carbon neutralization. Highlights: The upper and lower depth limits for kerogen to generate oil/gas worldwide are estimated by the equations with clear physical significance. The ratio of dissociation energy and molar mass of kerogen is one of the most critical factors for the upper and lower depth limits of oil/gas generated by kerogen.